2015
DOI: 10.1007/s00264-015-2935-z
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical analysis of stemless shoulder arthroplasty: a radiological study of seventy TESS total shoulder prostheses

Abstract: Stemless implants could be of help to reconstruct the shoulder anatomy. This study shows that there are some challenges to be addressed when attempting to ensure optimal implant positioning. The critical step is to determine the correct level of bone cut to avoid varus or valgus humeral head inclination and ensure correct head size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
2
24
1
Order By: Relevance
“…We used this best-fit circle to measure the deviation of the center of the prosthesis to the premorbid CoR. Previous studies demonstrated that a malpositioning of 3 to 4 mm can affect the clinical outcome[ 5 , 12 , 29 - 31 ]. According to Alolabi et al[ 12 ] and Kadum et al[ 31 ], we defined a deviation of 3 mm as clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…We used this best-fit circle to measure the deviation of the center of the prosthesis to the premorbid CoR. Previous studies demonstrated that a malpositioning of 3 to 4 mm can affect the clinical outcome[ 5 , 12 , 29 - 31 ]. According to Alolabi et al[ 12 ] and Kadum et al[ 31 ], we defined a deviation of 3 mm as clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the ability of different prosthetic designs to restore humeral head anatomy using several radiographic imaging modalities. 7,12,14,19 However, only one of these studies directly examined the relationship of stem length and postoperative humeral head anatomic restoration. 19 The purpose of this study was to examine the impact of humeral component stem length on the ability to restore the native humeral head anatomy after TSA.…”
mentioning
confidence: 99%
“…Even in the reverse configuration, studies report good results without loosening [12,16,17]. Anatomic stemless prostheses help to restore the pre-operative proximal humerus anatomy [18]. If the need for revision arises, stemless implants facilitate the surgical procedure as the bone stock is preserved.…”
Section: Discussionmentioning
confidence: 98%